OPTIMIZING OUTCOME OF DIABETES PATIENT CARE THROUGH HEALTH EDUCATION PROGRAMME: A LITERATURE REVIEW - Yusron Amin; Haswita Haswita (UPT Penerbitan Universitas Jember, 2023)
Background: Diabetes mellitus was still a current issue related to chronic disease care. increasing new cases and the failure of diabetes management made non optimally outcome of diabetes patient care. Health education programme was one of the solution of this. This study aims was to analyze the literature related to optimize outcome of diabetes patient care through health education programme. Methods: The study design was a literature review through using Pubmed, ScienceDirect, Proquest, and Google Scholar as database resources. Keyword used were diabetes patient care, health education programme, outcome. Inclusion criteria were original article, full text, provide about health education programme on diabetes patient, published five years recent (2018-2023), and written in English. Results: 12 articles selected from 434 articles. From which the result we analyze that health education programme had enhance knowledge, attitude, and practicing about glycemic control. This intervention was effective to control blood glucose level (HbA1c). The implementing of intervention was depended on three factors were type of intervention, methods, and periods. Conclusions: Health education programme was effective to optimize outcome of diabetes care. This outcome could be known from changing value of knowledge, attitude, practice, and glycemic control (blood glucose level). The effectivity of intervention was affected by type of intervention, methods, and periods. to optimize the result, need to use combine methods (structured education, social-media, and technology) in periods more than 6 months with strictly control to participants